Gender Inclusivity in Law Enforcement: Impact of Gender-Responsive Policing in Region IV-A, CALABARZON - Ophelia Doria Quilapio; Chester Alexis C. Buama; Maryjane D. Fuentes; Marie Anne S. Gonzales; Eden C. Callo; Marissa L. Dimarucot (Research Synergy Foundation, 2024)
This study investigates the status of gender equality in law enforcement, gender consideration and discrimination, gender safety in transportation, and the extent of gender-responsive policing. Employing a quantitative research design, the study sourced data from 165 participants through purposive sampling, which was sanctioned by the Land Transportation Office in Region IV-A CALABARZON. Findings reveal a young to middle-aged participant profile, predominantly with higher education, suggesting a potentially elevated perspective on gender inclusivity informed by their educational experiences. High mean scores across gender inclusivity metrics indicate a positive perception of gender equality, particularly in terms of economic participation, opportunities, and law enforcement practices. However, certain areas have highlighted the need for further research, especially regarding discrimination in career advancement. This study underscores the significant role of GROs in enhancing perceptions of gender equality and safety. This emphasizes the importance of fostering a positive community reception toward gender-responsive policing initiatives contrary to the initial hypotheses. Demographic profiles, including age and training received, were not significantly correlated with perceptions of gender-responsive policing, directing attention to areas warranting further investigation.